2011
DOI: 10.1097/mcg.0b013e3181eb5efd
|View full text |Cite
|
Sign up to set email alerts
|

Is Gastroduodenal Biopsy Safe in Patients Receiving Aspirin and Clopidogrel?

Abstract: Consistent with expert guidelines, the absolute risk attributable to gastroduodenal biopsy in adults taking antiplatelet agents seems to be low. Half of routine biopsies enter submucosa. The largest blood vessels avulsed during biopsy correspond to midsized and large arterioles and venules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Although several reports have indicated that aspirin alone in standard doses does not increase the rate of bleeding after an endoscopic biopsy,28, 29, 30 few prospective studies have appropriately evaluated the safety of antithrombotic therapy in patients undergoing an EGD biopsy. Ono et al 28 investigated hemostasis as well as late-phase bleeding risk in patients taking antithrombotic agents up to 2 weeks after an EGD biopsy, and found a low level of risk for either event in patients who continued antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several reports have indicated that aspirin alone in standard doses does not increase the rate of bleeding after an endoscopic biopsy,28, 29, 30 few prospective studies have appropriately evaluated the safety of antithrombotic therapy in patients undergoing an EGD biopsy. Ono et al 28 investigated hemostasis as well as late-phase bleeding risk in patients taking antithrombotic agents up to 2 weeks after an EGD biopsy, and found a low level of risk for either event in patients who continued antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size was relatively small. Previous studies have indicated that upper-GI bleeding related to a biopsy procedure is rare regardless of current administration of antithrombotic agents27, 28, 29, 30; thus, studies with a much larger scale are necessary to thoroughly investigate the proportion of patients taking antithrombotic agents who experience that complication and its risk compared with a control group. Unfortunately, we were not able to conduct such an investigation with an appropriate sample size to fully evaluate the study purpose.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the BSG-ESGE guideline recommends continuing aspirin for all endoscopic procedures with the exception of ESD, large colonic EMR (>2 cm), upper GI EMR, and ampullectomy, for which the risk of thrombosis versus hemorrhage should be individually balanced [8]. Although such an approach is generally safe, it should be noted that a bleeding episode requiring endoscopic treatment following multiple gastroduodenal biopsies occurred in 2.2% of 45 healthy volunteers receiving aspirin or clopidogrel monotherapy [54]. In a prospective study, a bleeding episode requiring endoscopic treatment was observed in 2.2% of 1015 patients who underwent cold polypectomy for the removal of <10 mm colonic polyps [56].…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…For less invasive endoscopic procedures such as biopsies, the risk of bleeding increases very little in patients taking antiplatelet agents [7-9], and even in patients on anticoagulant therapy the risk of postoperative hemorrhage is unchanged as long as the prothrombin time-international normalized ratio (PT-INR) is under 3.0 [10,11]. There is, however, a lack of consensus regarding more invasive procedures such as ESD.…”
Section: Introductionmentioning
confidence: 99%